(untitled) (Confluenţe Bibliologice, 2021)
The given article reports on the achievements of the aims and objectives of the Scientific Library during 2021 by promoting the image of the Library, continuous training of librarians’ professional skills, participation in international projects, offering high quality modern information services and products to all categories of users for sustainable development.